Human Rights Protection of Vulnerable Groups in Indonesia's Criminal Procedure Law - Robby Irawan; Muhammad Alwan Fillah; Burhanuddin Hamnach (Civiliza Publishing, 2026)
The protection of human rights for vulnerable groups has become a key priority in the reform of Indonesia's criminal procedural law, reflecting a shift from an offender-oriented justice system toward a human rights-based approach that ensures equal legal protection for all parties involved in criminal proceedings. This study aims to examine the protection of the rights of witnesses, victims, persons with disabilities, women, children, and older persons under the 2025 Indonesian Code of Criminal Procedure (KUHAP 2025) from a human rights perspective. This study employs a qualitative method using normative legal research with statutory, conceptual, and human rights approaches. The research relies on secondary data consisting of primary legal materials, legal literature, and supporting legal references collected through systematic library research and analyzed descriptively and analytically. The findings indicate that KUHAP 2025 significantly strengthens procedural safeguards for vulnerable groups by explicitly recognizing their rights and harmonizing domestic criminal procedural law with international human rights instruments, including the International Covenant on Civil and Political Rights (ICCPR), the Convention on the Rights of Persons with Disabilities (CRPD), and the Convention on the Rights of the Child (CRC). The study further reveals that the reform promotes victim-oriented, disability-inclusive, gender-sensitive, child-centered, and age-inclusive justice. However, its implementation remains constrained by institutional capacity, accessibility barriers, limited professional expertise, and persistent discriminatory legal culture. This study contributes both theoretically and practically by proposing an integrated human rights framework to strengthen institutional implementation and promote a more inclusive, equitable, and human rights-oriented criminal justice system in Indonesia.